Interaction design in collaborative Augmented Reality (AR) storybook for children / Lili Eliana Mohd Radzuan...[et.al] - Mohd Radzuan, Lili Eliana; Shamsudin, Wan Nur Khalisah; Razis, Siti NurIzaura; Harun, Azahar; Abd Razak, Mohamed Razeef (2016)
The study is to review some aspects within the field of human computer interaction (HCI) to be incorporated in the development of collaborative augmented reality applications with children’s storybook. The content analysis method was used to explore various theories and principles related to HCI. Thus, the review analysis and findings able to provide clear direction for future research and to contribute to the body of knowledge in this area.